2016
DOI: 10.15252/embr.201541708
|View full text |Cite
|
Sign up to set email alerts
|

TERRA promotes telomerase‐mediated telomere elongation in Schizosaccharomyces pombe

Abstract: Telomerase-mediated telomere elongation provides cell populations with the ability to proliferate indefinitely. Telomerase is capable of recognizing and extending the shortest telomeres in cells; nevertheless, how this mechanism is executed remains unclear. Here, we show that, in the fission yeast Schizosaccharomyces pombe, shortened telomeres are highly transcribed into the evolutionarily conserved long noncoding RNA TERRA. A fraction of TERRA produced upon telomere shortening is polyadenylated and largely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
78
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 41 publications
12
78
1
4
Order By: Relevance
“…6A,B), indicating that telomerase activity is indeed inhibited by TERRA in vivo. This is consistent with prior observations made biochemically in vitro (Schoeftner and Blasco, 2008; Redon et al, 2010; Moravec et al, 2016). ES cells naturally express high levels of TERRA, consistent with their long telomeres and a need to regulate telomere length.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…6A,B), indicating that telomerase activity is indeed inhibited by TERRA in vivo. This is consistent with prior observations made biochemically in vitro (Schoeftner and Blasco, 2008; Redon et al, 2010; Moravec et al, 2016). ES cells naturally express high levels of TERRA, consistent with their long telomeres and a need to regulate telomere length.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been hypothesized that TERRA in regulates telomerase in yeast (Pfeiffer and Lingner, 2012; Moravec et al, 2016). To determine whether TERRA affects telomerase activity in mammalian cells as well, we performed the Telomeric Repeat Amplification Protocol (TRAP) to quantitate telomerase activity in TERRA-depleted ES cells.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the demonstration that chromosomal lesions induced by incomplete DNA replication are sequestered in 53BP1-enriched nuclear compartments of G 1 cells to protect them from erosion ( 25 ), it is tempting to speculate that NRF1 may participate in telomere replication. One possibility would be that, on the basis of evidences obtained from budding and fission yeast ( 26 , 27 ), NRF1-dependent TERRA production may help in recruiting telomerase at chromosome ends to complete telomere synthesis. Alternatively, the transcription process per se may possibly help in resolving topological barriers at telomeres to promote replication fork progression.…”
Section: Resultsmentioning
confidence: 99%
“…RNA fluorescence in-situ hybridization (FISH) and live-cell imaging analyses have shown that a subset of TERRA transcripts localizes with human telomeres [5,6,17]. At telomeres, TERRA molecules have been proposed to mediate several important functions, including regulation of heterochromatin formation [16], recruitment of chromosome end-processing and chromatin remodelling factors to dysfunctional telomeres [18,19], sustaining telomeric DNA replication [20], participating in telomere length homeostasis by regulating telomerase activity [13,14] or promoting homologous recombination among telomeres through formation of RNA-DNA heteroduplex (R-loops) at chromosome ends [21-24]. In addition to their preferential association with telomeres, recent evidence indicates that TERRA transcripts interact with numerous internal chromosomal regions to regulate widespread gene expression [25].…”
Section: Introductionmentioning
confidence: 99%